Thermal nonreciprocity tuned by wrinkle patterns in graphene - Bohan Li; Qingxiang Ji; Qi Zhang; Changguo Wang; Muamer Kadic (New Journal of Physics)
Thermal nonreciprocity are typically realized by using nonlinear heat conductivity, external field bias or spatiotemporal modulation of thermal parameters, but these methods require specific material properties or accurate modulation means. Low-dimensional materials like graphene provides a platform to engineer heat transport characteristics at the molecular level. Here, by simply tuning graphene’s wrinkle morphology, the approach to generate nonreciprocal heat transfer is reported, which applies to both static and dynamic heat signals. Such nonreciprocity is attributed to the tunable responses of thermal conductivity on both temperatures and wrinkles. Phonon density of states of the wrinkled graphene exhibit distinct spectra, especially at the low frequency (around $17~THz$ ), which results in reduced temperature-sensitivity of thermal conductivities and eventually induces thermal nonreciprocity. The findings provide insights into the physics of thermal transport in wrinkled graphene, and paves a new avenue for mechanically modulating thermal nonreciprocity. Our method to obtain thermal nonreciprocity is reversible, tunable and controllable, meanwhile remains structural integrity, which benefits functional applications such as heat management in electronics.